2018
DOI: 10.1111/jvim.15389
|View full text |Cite
|
Sign up to set email alerts
|

The fecal microbiome and serum concentrations of indoxyl sulfate and p‐cresol sulfate in cats with chronic kidney disease

Abstract: Background Intestinal dysbiosis has been documented in humans with chronic kidney disease (CKD) and is thought to contribute to production of the uremic toxins indoxyl sulfate (IS) and p‐cresol sulfate (pCS). Characteristics of the fecal microbiome in cats with CKD and correlation to serum concentrations of uremic toxins are unknown. Objectives To characterize the fecal microbiome and measure serum IS and pCS concentrations of cats with CKD in comparison to healthy older cats. Animals Thirty client‐owned cats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 59 publications
1
43
2
1
Order By: Relevance
“…Further analyses on genus level revealed that compared with the other three groups, Bacteroides, Escherichia and Faecalibacterium was the dominant intestinal type in the PD group. Escherichia produce indoles which mainly affect the cardiovascular system and kidney functions and Faecalibacterium is one of the most abundant human fecal bacterial populations that produce butyrate, suggesting that PD treatment may increase toxins released in CKD patients [32,33]. With the accumulation of uremic toxins and activation of inflammatory reactions in CKD patients, there is a decrease in qualitative and quantitative properties of probiotics, which in turn promotes CKD progress [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Further analyses on genus level revealed that compared with the other three groups, Bacteroides, Escherichia and Faecalibacterium was the dominant intestinal type in the PD group. Escherichia produce indoles which mainly affect the cardiovascular system and kidney functions and Faecalibacterium is one of the most abundant human fecal bacterial populations that produce butyrate, suggesting that PD treatment may increase toxins released in CKD patients [32,33]. With the accumulation of uremic toxins and activation of inflammatory reactions in CKD patients, there is a decrease in qualitative and quantitative properties of probiotics, which in turn promotes CKD progress [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Further analyses on genus level revealed that compared with the other three groups, Bacteroides, Escherichia and Faecalibacterium was the dominant intestinal type in the PD group. Escherichia produce indoles which mainly affect the cardiovascular system and kidney functions and Faecalibacterium is one of the most abundant human fecal bacterial populations that produce butyrate, suggesting that PD treatment may increase toxins released in CKD patients [32] Gut microbiota can also affect immune system stimulation, intestinal epithelial homeostasis, vitamins B and K synthesis, gastrointestinal motility and function enhancement, nutrients absorption, drugs metabolism and SCFAs and polyamines production [4]. In our study, similar CKD and HD intestinal flora was correlated with similar expression of CRP and IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…This prospective, cross‐sectional study was performed at Colorado State University Veterinary Teaching Hospital. The same population of CKD and geriatric control cats was used in a previous publication evaluating the fecal microbiome using 16S ribosomal RNA gene sequencing and serum IS and pCS concentrations . To be eligible for inclusion, CKD and control cats underwent a thorough evaluation that included a review of the past medical record, complete physical examination (including 9‐point body condition score [BCS; Nestle Purina, St. Louis, Missouri] and muscle condition score [MCS]), minimum database consisting of CBC (Advia 120 Hematology System, Siemens Healthineers, Erlangen, Germany), serum biochemistry panel (Cobas 6000, Roche Diagnostics, Indianapolis, Indiana), and urinalysis, serum total thyroxine (T4) concentration, blood pressure, fecal flotation, and urine protein:creatinine ratio (UPC; Cobas 6000, Roche Diagnostics; if urine dipstick testing detected ≥1+ protein).…”
Section: Methodsmentioning
confidence: 99%
“…Although there is limited information regarding the microbiome and its link to kidney disease in veterinary medicine, cats with CKD have fecal dysbiosis characterized by decreased fecal microbial diversity and richness based on 16S ribosomal rRNA gene sequencing . Additionally, IS is increased in cats with CKD and is associated with disease progression, and in some CKD cats, serum pCS concentrations are increased compared to healthy geriatric controls . However, to date, fecal SCFA concentrations have not been characterized in cats with CKD.…”
Section: Introductionmentioning
confidence: 99%